(untitled) (Global Journal of Science Frontier Research, 2020)
In the article, based on the principle of counter-directionality of nonequilibrium processes and the law of conservation of energy, it is shown that evolutionary processes in some parts (areas, phases, components) of an isolated system are impossible without the involution of others. The simultaneity and opposite direction of these processes are proved, confirming their dialectical unity and the creative tendency inherent in nature. The inapplicability of entropy as a criterion for evolution is emphasized, and its non-entropy criteria are proposed both for systems as a whole and for each degree of their freedom. Examples of "coupled" processes of evolution and involution in objects of animate and inanimate nature are given. The erroneousness of the concept of the origin of "order" from "chaos" and the inapplicability of the concept of "arrow of time" to the Universe as a whole is substantiated.